(untitled) (Inovasi, 2023)
Stunting is a global issue. Indonesia is one of the countries having a big burden on stunting problems in the Southeast Asian region and in the world. The stunting prevalence trend in Indonesia shows a decrease, yet it is dominated more by direct intervention to the children who are sufferers of stunting and who are not, less than 5 years old. The impact such as this is not permanent because the program does not involve the pregnant women or the mothers of those children, who are the closest figures to every children. One of the stunting contexts that is being ignored all this time is fulfilling the rights of sexual health and gender equality to mothers. Before having their family, during pregnancy, and when raising their children, many women reproductive’s right are ignored and even put aside. Finally, the optimal health of mothers and children less than 5 years old is never achieved. This paper discusses those rights and explains the relation with the stunting problems. As discussed in this paper, it is shows that the government is not successful in providing services that fulfill women’s rights. Many health services are in fact not impartial or even inaccessible to women. Thus, the government actually contributes significantly to the non- fulfillment of women’s rights. This paper recommends that efforts to reduce the prevalence of stunting are not only from health perspective. Empowerment of women through women’s groups is important to put forward. It is also important for the government to fulfill the right to reproductive health through the reconstruction of norms in society through state institutions. In addition, the government must ensure the fulfillment of health services that are stand on women’s side. Only by this ways, stunting can be prevented in the future. Keywords: stunting, reproductive health right, gender, Indonesia